Desires in Paradise: an interpretative study of Augustine's City of God 14 - Trettel, Adam (Augustinus - Werk und Wirkung, 2019)
For Augustine, the pre-Fall Paradise was a life of tranquil love and joy. The post-Fall world is marked by loss of control over our bodies and emotions. But what exactly happened in the Fall, and why? How does desire relate to man’s disobedience, and is there any sense in which we can recover what Adam and Eve have lost? In treating City 14 as an integral whole, this study explores Augustine’s critiques of the Manichean and Platonist positions that the body is bad or evil, and dis-cusses his biblical doctrine of emotions in light of the two-cities theme. The entire study concerns topics germane to the paradisal situation: the theme of the Primal Fall and the will being ‘spontaneous’, the exploration of the disobedience of the genitals in all forms of sex, including married life, and the workings of Adam and Eve’s hypothetical sexual experience in the pre-Fall world.